Coaching, Mentoring and Managing Leadership for Beginning Counselor - Salhah Abdullah; Sapora Sipon (Universiti Sains Islam Malaysia, 2024)
This qualitative case study is designed to explore the application of basic counseling skills for beginning counselor (BC). Eleven counseling students participated in this study which comprised of eight second year students as mentees and three third year students as mentors. The objective of this study is to explore the application of basic counseling skills in conducting individual counseling sessions with the client from first year counseling students. Content analysis was used to identify themes from two documents based on transcriptions of counseling sessions and self reflection journals. The theme emerges from the analysis of data shown the strength and weaknesses of BC applying basic counseling skills. This study has implications for professional development of counseling students including; (1) The role of peer mentor which provides emotional and professional support to BC (2) peer mentoring and coaching project enhance self-efficacy, and (3) continuous development of self-efficacy and competency for BC. Future study suggests an intervention for both mentors and mentee in order to enhance professional competency of counseling Future studies are recommended to include group counseling which involve first year counseling student as member of the group counseling. Finally, this study proposes to develop module of coaching and mentoring for beginning counselor.